Pejorative phrases or innocent idioms? Exploring terms used by tomorrow's doctors in relation to older people. Issue 9 (2nd September 2018) - Fisher, James M; Tullo, Ellen; Stewart, Jane
ABSTRACT: Older people are the "core business" for 21st century hospitals. Of concern, therefore, is negative stereotyping of older people by medical students. Through a bespoke teaching session for final-year medical students, we aimed to deconstruct the phraseology they employed in relation to older people and to drive attitudinal change among students. This study also aimed to discern whether there was a detectable difference in attitudes toward older people after the session. Forty-seven medical students participated. Students recorded in a "word-cloud" terms they associated with older people in hospital before and after the session. The University of California Los Angeles Geriatrics Attitude Scale (UCLA-GAS) was administered for pre-session. The intervention students, along with a control group, completed this instrument at the end of their placement. Content analysis of word cloud data was performed—an iterative, transparent, structured approach to analysis, along with external critique of findings and collaborative triangulation ensured rigor of analysis. Qualitative analysis demonstrated the use of pejorative and sometimes nihilistic terms. There were evidence of growing appreciation of the inherent complexity of caring for older people and increasing awareness of how healthcare systems can be challenging for older people. Quantitative analysis revealed that there is no statistical difference neither between the UCLA-GAS pre- and post-teaching nor the intervention and control groups. In conclusion, a bespoke educational intervention, designed to promote student reflection on their views toward older people in hospital, can be a catalyst to challenging superficial and stereotypical views.